Lysine granules and preparation method thereof
By employing a three-layer coating technology, the problem of lysine's tendency to absorb moisture and clump is solved, achieving stable storage and efficient release of lysine particles, thereby improving the product's storage stability and bioavailability.
Patent Information
- Application Number
- CN202511114592.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-11
- Publication Date
- 2025-11-11
AI Technical Summary
Existing lysine production processes cannot effectively control crystal form, resulting in products that are prone to moisture absorption and clumping. Furthermore, existing improvement methods such as drying, adding anti-caking agents, or coating have side effects, affecting product stability and bioavailability.
The product employs a three-layer coating technology: the inner layer uses microcrystalline cellulose as a framework, the middle layer uses glycerol as a moisture barrier, and the outer layer is an enteric coating. This synergistic effect ensures the stability and bioavailability of the particles during storage and release.
It significantly improves the storage stability and bioavailability of lysine particles, avoids clumping, achieves targeted release, and is suitable for long-term storage and efficient utilization in humid environments.
Abstract
Description
Technical Field
[0001] This application relates to the field of lysine technology, and mainly to a lysine particle and its preparation method. Background Technology
[0002] Lysine, an essential amino acid indispensable for human and animal growth and development, plays a crucial role in protein synthesis, nutritional metabolism regulation, and immune function enhancement. In the feed industry, lysine is an important feed additive that effectively supplements the lysine deficiency in grain feed, improves animal protein utilization, and promotes animal growth. In the food industry, lysine is also frequently used to fortify the nutritional value of food and meet the human body's amino acid requirements.
[0003] Currently, the most commonly used lysine product in industry is L-lysine hydrochloride, whose production process is relatively mature and cost-effective. However, existing lysine production processes cannot effectively control crystal form, resulting in the potential presence of multiple crystal forms in the product. These different crystal forms exhibit variations in solubility, hygroscopicity, and stability, with some forms being more prone to absorbing moisture and agglomerating, affecting product storage and use. Furthermore, the presence of free amino and carboxyl groups on the surface of lysine particles makes them susceptible to interaction with moisture in the air, further exacerbating the hygroscopic agglomeration phenomenon.
[0004] To improve the physical properties and stability of lysine, various methods have been developed, including drying, adding anti-caking agents, and coating. While drying can temporarily reduce the water content of lysine, it cannot fundamentally solve the moisture absorption problem. Adding anti-caking agents can prevent particle adhesion to some extent, but the type and amount of anti-caking agent significantly affect the effect, and some anti-caking agents may have adverse health effects. Coating technology is a commonly used modification method that prevents water molecule penetration and clumping by covering the surface of lysine particles with a protective layer. However, the coating material itself introduces new problems, such as affecting the release rate or bioavailability of lysine. Some coating materials may be difficult to dissolve in the digestive tract, resulting in insufficient release of lysine and reduced bioavailability.
[0005] Therefore, existing technologies still need to be improved and developed. Summary of the Invention
[0006] In view of the shortcomings of the prior art, the purpose of this application is to provide lysine particles and a method for preparing the same, in order to improve the problem of lysine particles easily absorbing moisture and clumping together.
[0007] The technical solution of this application is as follows: A method for preparing lysine granules includes the following steps: Inner layer preparation: L-lysine hydrochloride and microcrystalline cellulose are mixed at 500-800 rpm, then an adhesive solution is added, and the mixture is stirred until it reaches a soft state. After drying, the first-stage particles are obtained. Intermediate coating: Glycerin, sodium bicarbonate, and alcohol solution A are mixed to obtain an intermediate coating solution; the intermediate coating solution is sprayed onto the surface of the first-stage particles, and the coating weight gain is controlled at 8-12%; then dried and cured to obtain the second-stage particles; Outer layer preparation: Eudragit L100, anti-adhesion agent, plasticizer, and alcohol solution B are mixed to obtain an outer coating liquid; then the outer coating liquid is sprayed onto the surface of the second-stage particles, and the coating weight gain is controlled at 15-20% to obtain the lysine particles.
[0008] The lysine granules of this application feature a tightly integrated, synergistic structure. The inner layer, with microcrystalline cellulose as its framework, is mixed with L-lysine hydrochloride to provide a stable structure and ensure uniform distribution of the active ingredient. The middle layer, a coating solution, forms a moisture barrier, reducing hygroscopic absorption and preventing clumping and deterioration during storage. Its flexibility also buffers subsequent gas production pressure. The outer layer uses a coating solution made with Eudragit L100, which dissolves in the specific pH environment of the intestine, achieving targeted release of lysine and avoiding destruction by gastric acid. The three layers have clearly defined functions: the inner layer provides basic support, the middle layer ensures storage stability, and the outer layer controls the release timing. This layered approach enhances the stability and bioavailability of the lysine granules, enabling them to exert their effects more effectively.
[0009] Specifically, the inner layer of microcrystalline cellulose (MCC) plays a crucial role in structural support and accelerating disintegration. As a porous framework material, it forms a high-porosity structure within the particles through hydrogen bonding and capillary action. Upon contact with water, the hydrophilicity of MCC allows it to wet rapidly, with water penetrating into the particle interior via capillary action, disrupting the interparticle bonds. Simultaneously, its compressibility ensures that the particles maintain structural integrity under pressure, preventing premature disintegration. Furthermore, the porous structure of MCC provides gas diffusion channels for sodium bicarbonate gas production, ensuring uniform gas release and promoting rapid particle disintegration.
[0010] Glycerin is the core component of the middle layer plasticizer and moisture barrier. As a small-molecule hydrophilic plasticizer, it effectively reduces intermolecular forces, giving the particles flexibility. Glycerin forms hydrogen bonds with the hydroxyl groups of MCC, reducing the exposure of hydrophilic groups on the particle surface, reducing hygroscopicity, and preventing clumping or deterioration during storage. The flexible film layer formed by glycerin can also buffer the internal pressure when sodium bicarbonate produces gas, preventing particle breakage, ensuring slow gas release, and extending the action time.
[0011] Sodium bicarbonate is key to gas generation and pH regulation. As a gas-generating agent, it reacts with acid to produce carbon dioxide gas, creating internal pressure that drives particle disintegration. This application employs enteric coating, allowing sodium bicarbonate to trigger gas generation under specific pH conditions in the intestine, achieving targeted release of lysine. Its gas generation reaction relies on the porous structure of MCC to provide a gas diffusion path, while the flexible membrane layer of glycerol controls the gas release rate, preventing particle breakage due to sudden gas release.
[0012] In summary, the three-layer coating structure achieves functional stratification and synergistic enhancement. The inner layer, the MCC framework, provides structural support, ensuring the integrity of the particles under pressure, while also providing a gas diffusion channel for the gas-generating reaction. The middle layer, the glycerol membrane, acts as a plasticizer and moisture barrier, buffering the gas-generating pressure, preventing the particles from absorbing moisture and clumping, and extending storage stability. The outer layer, the enteric coating, controls the gas-generating trigger conditions, enabling targeted release of lysine and protecting the particles from gastric acid damage. The three-layer structure achieves synergistic optimization of "structure-moisture-generating" through functional stratification: the MCC ensures the basis for particle disintegration, the glycerol membrane regulates the gas-generating rate, and the enteric coating controls the release timing.
[0013] Furthermore, the mass ratio of the L-lysine hydrochloride to the microcrystalline cellulose is 1:(1.2-1.5).
[0014] Furthermore, the adhesive solution comprises one or a mixture of two of the following: an aqueous solution of hydroxypropyl methylcellulose, an aqueous solution of sodium carboxymethyl cellulose, and an aqueous solution of hydroxypropyl cellulose. The adhesive solution has a mass concentration of 5-10%.
[0015] Furthermore, according to the mass percentage of the intermediate coating solution, the glycerol is 15-25%, the sodium bicarbonate is 0.1-0.5%, and the balance is alcohol solution A.
[0016] Furthermore, when spraying the intermediate coating liquid onto the surface of the first-stage particles, the intermediate coating liquid is sprayed at a rate of 6-8 mL / min, while hot air at 40-45°C is introduced for drying.
[0017] Furthermore, the drying and curing conditions for the middle layer coating are 25-35℃ for 3-5 hours.
[0018] Furthermore, according to the mass percentage of the outer coating liquid, the Eudragit L100 is 5-15%, the anti-adhesive is 1-3%, the plasticizer is 0.1-1%, and the balance is alcohol solution B.
[0019] Furthermore, the anti-adhesion agent can be one or more of talc, titanium dioxide, and stearic acid.
[0020] Furthermore, the plasticizer can be one or more of triethyl citrate, triacetin, and triethyl citrate, or a mixture thereof.
[0021] Furthermore, when spraying the outer coating liquid onto the surface of the second-stage particles, the outer coating liquid is sprayed at a rate of 4-6 mL / min, while hot air at 35-40°C is introduced for drying.
[0022] Furthermore, after the outer layer is prepared, it is placed at room temperature for 12-36 hours to obtain the lysine particles.
[0023] This application also provides a lysine particle.
[0024] Compared with the prior art, this application has the following beneficial effects: 1. Glycerin, as a hydrophilic plasticizer, forms hydrogen bonds with the hydroxyl groups of the inner microcrystalline cellulose (MCC), reducing the exposure of hydrophilic groups on the particle surface and thus lowering its moisture adsorption capacity. Furthermore, the flexible membrane layer formed inside the glycerin particles acts as a physical moisture barrier, effectively preventing moisture penetration from the environment. This ensures the structural integrity and activity stability of the lysine particles during storage, making them particularly suitable for long-term storage in humid environments.
[0025] 2. The unique three-layer structure of lysine particles significantly improves the bioavailability of lysine through the synergistic effect of targeted release and accelerated disintegration. The outer layer remains intact in the acidic environment of the stomach (pH < 5.5), preventing lysine from being destroyed by gastric acid; upon entering the intestine (pH > 6.0), it dissolves rapidly, achieving precise release. The porous structure of the inner MCC framework provides gas diffusion channels for sodium bicarbonate, and the carbon dioxide generated by the gas production reaction drives the rapid disintegration of the particles, enabling efficient release of lysine in the intestine. The middle glycerol membrane buffers the gas production pressure, preventing the particles from breaking due to sudden gas release, ensuring a stable and controllable release process.
[0026] 3. The three-layer coating structure of lysine granules, through functional stratification and material synergy, endows the granules with excellent storage stability. The inner MCC framework provides mechanical support, ensuring the granules remain intact under pressure or vibration; the middle glycerol film acts as a moisture barrier and plasticizer, reducing hygroscopicity through hydrogen bonding while buffering gas generation pressure, preventing granule rupture due to changes in environmental humidity or internal gas release; the outer enteric coating isolates oxygen and light, delaying the oxidative degradation of the active ingredient. The unique structure of lysine granules allows for long-term stable storage under normal temperature or fluctuating temperature and humidity conditions, significantly reducing quality risks. Detailed Implementation
[0027] To facilitate understanding of this application, the following embodiments are provided. Those skilled in the art should understand that these embodiments are merely illustrative and should not be construed as limiting the scope of this application.
[0028] This application provides a method for preparing lysine particles, comprising the following steps: Step 1: Inner layer preparation, specifically including the following steps: Step 1a: Add L-lysine hydrochloride and microcrystalline cellulose (MCC) to a high-speed mixer at a mass ratio of 1:(1.2-1.5) and mix at 500-800 rpm for 10-15 minutes to ensure that the MCC uniformly coats the L-lysine hydrochloride.
[0029] Mixed particles are obtained.
[0030] Step 1b: Slowly add the adhesive solution to the mixed particles and stir until it reaches a soft state (it can be formed into a ball by hand and easily crumbles when pressed lightly).
[0031] Then, the particles are granulated through a sieve to ensure uniformity and avoid excessive fine powder that could affect subsequent coating.
[0032] The adhesive solution includes one or a mixture of two of the following: aqueous solution of hydroxypropyl methylcellulose, aqueous solution of sodium carboxymethyl cellulose, and aqueous solution of hydroxypropyl cellulose.
[0033] The mass concentration of the adhesive solution is 5-10%.
[0034] Step 1c: Dry the particles obtained in step 1b in a forced-air drying oven at 55-60℃ for 2-3 hours until the moisture content is ≤2.5% to avoid high temperature damaging the activity of lysine.
[0035] The first-stage particles were obtained.
[0036] Step 2: Middle layer coating, specifically including the following steps: Step 2a: Mix glycerol and sodium bicarbonate until homogeneous, and then mix with 95% ethanol to prepare a middle coating solution for later use.
[0037] The intermediate coating solution comprises, by mass percentage, 15-25% glycerol, 0.1-0.5% sodium bicarbonate, and the remainder ethanol.
[0038] Step 2b: Place the first-stage particles in a fluidized bed and spray the intermediate coating solution at a rate of 6-8 mL / min, while simultaneously introducing hot air at 40-45℃ for drying.
[0039] The weight gain of the coating is controlled at 8%-12% to ensure the uniformity of the film layer.
[0040] Step 2c: Place the coated particles obtained in step 2b in an oven at 25-35℃ for 3-5 hours to allow glycerol and MCC hydroxyl groups to fully bond with hydrogen bonds, thereby enhancing the stability of the film layer.
[0041] Second-stage particles were obtained.
[0042] Step 3: Outer layer preparation, specifically including the following steps: Step 3a: Dissolve Eudragit L100 (acrylic resin II), anti-adhesive, and plasticizer in 95% ethanol to prepare an outer coating solution for later use.
[0043] The outer coating liquid consists of 5-15% Eudragit L100, 1-3% anti-adhesive, 0.1-1% plasticizer, and the remainder is ethanol, based on the mass percentage of the outer coating liquid.
[0044] The anti-sticking agent can be one or more of talc, titanium dioxide, and stearic acid.
[0045] The plasticizer can be one or more of triethyl citrate, triacetin, and triethyl citrate, or a mixture thereof.
[0046] Step 3b: Place the second-stage particles in a fluidized bed and spray the outer coating liquid at a rate of 4-6 mL / min, while simultaneously introducing hot air at 35-40℃ for drying.
[0047] The weight gain of the coating is controlled at 15%-20% to ensure the integrity of the outer film.
[0048] Step 3c: Let the coated particles from step 3b stand at room temperature for 12-36 hours to eliminate residual stress and prevent the film from cracking, thus obtaining lysine particles.
[0049] The present application will be further described below through specific embodiments.
[0050] Example 1: This application provides a method for preparing lysine particles, comprising the following steps:
[0051] Step 1: Inner layer preparation, specifically including the following steps: Step 1a: Add L-lysine hydrochloride (purchased from Shandong Xinxiong Biotechnology Co., Ltd., food grade) and microcrystalline cellulose (purchased from DuPont, model Avicel PH-101) to a high-speed mixer at a mass ratio of 1:1.3 and mix at 600 rpm for 12 minutes to obtain mixed particles.
[0052] Step 1b: Slowly add 8% hydroxypropyl methylcellulose aqueous solution to the mixed granules, stir until a soft mass is formed, and then granulate through a sieve.
[0053] Hydroxypropyl methylcellulose was purchased from Zhejiang Yicun Biotechnology Co., Ltd., and is food grade.
[0054] Step 1c: Dry the particles obtained in step 1b in a 58°C forced-air drying oven for 2.5 hours until the moisture content is ≤2.5%, to obtain the first-stage particles.
[0055] Step 2: Middle layer coating, specifically including the following steps: Step 2a: Mix glycerol and sodium bicarbonate until homogeneous, and then mix with 95% ethanol to prepare a middle coating solution for later use.
[0056] Based on the mass percentage of the intermediate coating solution, the glycerol is 20%, the sodium bicarbonate is 0.3%, and the ethanol is 79.7%.
[0057] Step 2b: Place the first-stage particles in a fluidized bed, spray the intermediate coating liquid at a rate of 7 mL / min, and simultaneously pass in hot air at 42°C for drying.
[0058] The weight gain from the coating is 10%.
[0059] Step 2c: Place the coated granules obtained in step 2b in a 30°C oven for 4 hours to obtain the second-stage granules.
[0060] Step 3: Outer layer preparation, specifically including the following steps: Step 3a: Dissolve Eudragit L100 (acrylic resin II), talc (purchased from Hebei Tuohai Biotechnology Co., Ltd., food grade), and triethyl citrate (purchased from Hubei Langbowan Biomedical Co., Ltd., food grade) in 95% ethanol to prepare an outer coating solution for later use.
[0061] Based on the mass percentage of the outer coating liquid, Eudragit L100 is 10%, talc is 2%, triethyl citrate is 0.5%, and ethanol is 87.5%.
[0062] Step 3b: Place the second-stage particles in a fluidized bed, spray the outer coating liquid at a rate of 5 mL / min, and simultaneously pass in hot air at 38°C for drying.
[0063] The weight gain from the coating is controlled at 18%.
[0064] Step 3c: Let the coated particles from step 3b stand at room temperature for 24 hours to eliminate residual stress and prevent the film from cracking, thus obtaining lysine particles.
[0065] Performance testing: 1. Hygroscopicity: The initial moisture content of lysine particles (sample) was determined, and then the sample was placed in a constant temperature and humidity chamber with a relative humidity of 90%±2% and a temperature of 30℃±1℃. After 7 days, the sample was taken out and the hygroscopicity was measured.
[0066] The formula for calculating the moisture absorption rate is: Moisture absorption rate = (W2 - W1) / W1 × 100%, where W1 is the initial weight of the sample and W2 is the weight of the sample after moisture absorption. Test results: The moisture absorption rate after 7 days is 2.0%.
[0067] 2. Lysine release rate: Referring to the dissolution test method of Part IV of the 2020 edition of the Chinese Pharmacopoeia, the gastrointestinal fluid environment was simulated, and the paddle method was used with a rotation speed of 100 rpm. Samples were taken at 120 minutes to determine the amount of lysine released.
[0068] Test results: Lysine release rate (120 minutes) was 95%.
[0069] 3. Disintegration effect: (1) Gastric juice simulation (pH 1.2, 37℃): the outer membrane is intact and the inner particles do not disintegrate (≤1% dissolution).
[0070] (2) Intestinal fluid simulation (pH 6.8, 37℃): After the outer layer dissolves, the inner layer particles completely disintegrate within 15 minutes (dissolution rate ≥ 90%).
[0071] 4. Stability: After being placed at 40℃ / 75%RH for 6 months, the lysine content of the lysine particles was tested (decline rate ≤5%). The stability was good and there was no clumping.
[0072] Example 2: This application provides a method for preparing lysine particles, comprising the following steps: Step 1: Inner layer preparation, specifically including the following steps: Step 1a: Add L-lysine hydrochloride and microcrystalline cellulose to a high-speed mixer at a mass ratio of 1:1.2 and mix at 600 rpm for 12 minutes to obtain mixed particles.
[0073] Step 1b: Slowly add 10% hydroxypropyl methylcellulose aqueous solution to the mixed particles, stir until a soft mass is formed, and then granulate through a sieve.
[0074] Step 1c: Dry the particles obtained in step 1b in a 58°C forced-air drying oven for 2.5 hours until the moisture content is ≤2.5%, to obtain the first-stage particles.
[0075] Step 2: Middle layer coating, specifically including the following steps: Step 2a: Mix glycerol and sodium bicarbonate until homogeneous, and then mix with 95% ethanol to prepare a middle coating solution for later use.
[0076] Based on the mass percentage of the intermediate coating solution, the glycerol is 15%, the sodium bicarbonate is 0.1%, and the ethanol is 84.9%.
[0077] Step 2b: Place the first-stage particles in a fluidized bed, spray the intermediate coating liquid at a rate of 7 mL / min, and simultaneously pass in hot air at 42°C for drying.
[0078] The weight gain from the coating was 12%.
[0079] Step 2c: Place the coated granules obtained in step 2b in a 30°C oven for 4 hours to obtain the second-stage granules.
[0080] Step 3: Outer layer preparation, specifically including the following steps: Step 3a: Dissolve Eudragit L100 (acrylic resin II), talc, and triethyl citrate in 95% ethanol to prepare an outer coating solution for later use.
[0081] Based on the mass percentage of the outer coating liquid, Eudragit L100 is 5%, talc is 1%, triethyl citrate is 0.1%, and ethanol is 93.9%.
[0082] Step 3b: Place the second-stage particles in a fluidized bed, spray the outer coating liquid at a rate of 5 mL / min, and simultaneously pass in hot air at 38°C for drying.
[0083] The weight gain from coating is controlled at 20%.
[0084] Step 3c: Let the coated particles from step 3b stand at room temperature for 24 hours to eliminate residual stress and prevent the film from cracking, thus obtaining lysine particles.
[0085] The raw materials used in this application are the same as those in Example 1.
[0086] Performance testing: 1. Hygroscopicity: The initial moisture content of lysine particles (sample) was determined, and then the sample was placed in a constant temperature and humidity chamber with a relative humidity of 90%±2% and a temperature of 30℃±1℃. After 7 days, the sample was taken out and the hygroscopicity was measured.
[0087] The formula for calculating the moisture absorption rate is: Moisture absorption rate = (W2 - W1) / W1 × 100%, where W1 is the initial weight of the sample and W2 is the weight of the sample after moisture absorption. Test results: The moisture absorption rate after 7 days is 2.6%.
[0088] 2. Lysine release rate: Referring to the dissolution test method of Part IV of the 2020 edition of the Chinese Pharmacopoeia, the gastrointestinal fluid environment was simulated, and the paddle method was used with a rotation speed of 100 rpm. Samples were taken at 120 minutes to determine the amount of lysine released.
[0089] Test results: Lysine release rate (120 minutes) was 92%.
[0090] 3. Disintegration effect: (1) Gastric juice simulation (pH 1.2, 37℃): the outer membrane is intact and the inner particles do not disintegrate (≤1% dissolution).
[0091] (2) Intestinal fluid simulation (pH 6.8, 37℃): After the outer layer dissolves, the inner layer particles completely disintegrate within 15 minutes (dissolution rate ≥ 90%).
[0092] 4. Stability: After being placed at 40℃ / 75%RH for 6 months, the lysine content of the lysine particles was tested (decline rate ≤5%). The stability was good and there was no clumping.
[0093] Example 3: This application provides a method for preparing lysine particles, comprising the following steps: Step 1: Inner layer preparation, specifically including the following steps: Step 1a: Add L-lysine hydrochloride and microcrystalline cellulose to a high-speed mixer at a mass ratio of 1:1.5 and mix at 600 rpm for 12 minutes to obtain mixed particles.
[0094] Step 1b: Slowly add 5% hydroxypropyl methylcellulose aqueous solution to the mixed granules, stir until a soft mass is formed, and then granulate through a sieve.
[0095] Step 1c: Dry the particles obtained in step 1b in a 58°C forced-air drying oven for 2.5 hours until the moisture content is ≤2.5%, to obtain the first-stage particles.
[0096] Step 2: Middle layer coating, specifically including the following steps: Step 2a: Mix glycerol and sodium bicarbonate until homogeneous, and then mix with 95% ethanol to prepare a middle coating solution for later use.
[0097] The intermediate coating solution comprises, by mass percentage, 25% glycerol, 0.5% sodium bicarbonate, and 74.5% ethanol.
[0098] Step 2b: Place the first-stage particles in a fluidized bed, spray the intermediate coating liquid at a rate of 7 mL / min, and simultaneously pass in hot air at 42°C for drying.
[0099] The weight gain from the coating was 8%.
[0100] Step 2c: Place the coated granules obtained in step 2b in a 30°C oven for 4 hours to obtain the second-stage granules.
[0101] Step 3: Outer layer preparation, specifically including the following steps: Step 3a: Dissolve Eudragit L100 (acrylic resin II), talc, and triethyl citrate in 95% ethanol to prepare an outer coating solution for later use.
[0102] Based on the mass percentage of the outer coating liquid, Eudragit L100 is 15%, talc is 3%, triethyl citrate is 1%, and ethanol is 81%.
[0103] Step 3b: Place the second-stage particles in a fluidized bed, spray the outer coating liquid at a rate of 5 mL / min, and simultaneously pass in hot air at 38°C for drying.
[0104] The weight gain from coating is controlled within 15%.
[0105] Step 3c: Let the coated particles from step 3b stand at room temperature for 24 hours to eliminate residual stress and prevent the film from cracking, thus obtaining lysine particles.
[0106] The raw materials used in this application are the same as those in Example 1.
[0107] Performance testing: 1. Hygroscopicity: The initial moisture content of lysine particles (sample) was determined, and then the sample was placed in a constant temperature and humidity chamber with a relative humidity of 90%±2% and a temperature of 30℃±1℃. After 7 days, the sample was taken out and the hygroscopicity was measured.
[0108] The formula for calculating the moisture absorption rate is: Moisture absorption rate = (W2 - W1) / W1 × 100%, where W1 is the initial weight of the sample and W2 is the weight of the sample after moisture absorption. Test results: The moisture absorption rate after 7 days is 2.5%.
[0109] 2. Lysine release rate: Referring to the dissolution test method of Part IV of the 2020 edition of the Chinese Pharmacopoeia, the gastrointestinal fluid environment was simulated, and the paddle method was used with a rotation speed of 100 rpm. Samples were taken at 120 minutes to determine the amount of lysine released.
[0110] Test results: Lysine release rate (120 minutes) was 91%.
[0111] 3. Disintegration effect: (1) Gastric juice simulation (pH 1.2, 37℃): the outer membrane is intact and the inner particles do not disintegrate (≤1% dissolution).
[0112] (2) Intestinal fluid simulation (pH 6.8, 37℃): After the outer layer dissolves, the inner layer particles completely disintegrate within 15 minutes (dissolution rate ≥ 90%).
[0113] 4. Stability: After being placed at 40℃ / 75%RH for 6 months, the lysine content of the lysine particles was tested (decline rate ≤5%). The stability was good and there was no clumping.
[0114] Comparative Example 1 The following tests were performed on commercially available, food-grade L-lysine hydrochloride: 1. Hygroscopicity: The initial moisture content of L-lysine hydrochloride (sample) was determined, and then the sample was placed in a constant temperature and humidity chamber with a relative humidity of 90%±2% and a temperature of 30℃±1℃. After 7 days, the sample was taken out and the hygroscopicity was measured.
[0115] The formula for calculating the moisture absorption rate is: Moisture absorption rate = (W2 - W1) / W1 × 100%, where W1 is the initial weight of the sample and W2 is the weight of the sample after moisture absorption. Test results: The moisture absorption rate after 7 days is 8.5%.
[0116] 2. Lysine release rate: Referring to the dissolution test method of Part IV of the 2020 edition of the Chinese Pharmacopoeia, the gastrointestinal fluid environment was simulated, and the paddle method was used with a rotation speed of 100 rpm. Samples were taken at 120 minutes to determine the amount of lysine released.
[0117] Test results: Lysine release rate (120 minutes) was 97%.
[0118] 3. Stability: After being placed at 40℃ / 75%RH for 6 months, the lysine content of the lysine particles was tested. The results showed a decrease rate of >5%, indicating poor stability and severe clumping.
[0119] Comparative Example 2 The following tests were performed on commercially available coated L-lysine hydrochloride: 1. Hygroscopicity: The initial moisture content of lysine particles (sample) was determined, and then the sample was placed in a constant temperature and humidity chamber with a relative humidity of 90%±2% and a temperature of 30℃±1℃. After 7 days, the sample was taken out and the hygroscopicity was measured.
[0120] The formula for calculating the moisture absorption rate is: Moisture absorption rate = (W2 - W1) / W1 × 100%, where W1 is the initial weight of the sample and W2 is the weight of the sample after moisture absorption. Test results: The moisture absorption rate after 7 days is 6.4%.
[0121] 2. Lysine release rate: Referring to the dissolution test method of Part IV of the 2020 edition of the Chinese Pharmacopoeia, the gastrointestinal fluid environment was simulated, and the paddle method was used with a rotation speed of 100 rpm. Samples were taken at 120 minutes to determine the amount of lysine released.
[0122] Test results: Lysine release rate (120 minutes) was 75%.
[0123] 3. Disintegration effect: (1) Gastric juice simulation (pH 1.2, 37℃): the outer membrane is relatively intact, and the inner particles do not disintegrate significantly (1-5% dissolution).
[0124] (2) Intestinal fluid simulation (pH 6.8, 37℃): the outer layer dissolves, and the inner layer particles cannot completely disintegrate within 15 minutes (dissolution rate ≥ 90%).
[0125] 4. Stability: After being placed at 40℃ / 75%RH for 6 months, the lysine content of the lysine particles was tested (decline rate ≤5%). The stability was good, with slight and small amount of clumping.
[0126] Comparing the test data of Examples 1-3 with Comparative Example 1, it can be seen that commercially available, food-grade L-lysine hydrochloride is highly hygroscopic and has poor storage properties under high temperature and high humidity. Examples 1-3 provided in this application can effectively alleviate the problem of severe hygroscopicity of L-lysine hydrochloride, and the release rate of lysine does not decrease much, and it also has good storage effect under high temperature and high humidity.
[0127] Combined with the test data of Comparative Example 2, it can be seen that although commercially available coated L-lysine hydrochloride has some improvement in hygroscopicity and stability compared with commercially available and food-grade L-lysine hydrochloride, it is significantly inferior to the effect of this application; the disintegration effect is also inferior to that of this application. Moreover, the lysine release effect of Comparative Example 2 is significantly different from that of commercially available and food-grade L-lysine hydrochloride and this application, and the effect is not good.
[0128] In summary, the technical solution provided in this application can produce lysine particles with good moisture absorption, fast lysine release rate, good disintegration effect, and excellent high temperature and high humidity storage properties.
[0129] It should be understood that the application of this application is not limited to the examples above. Those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of this application.
Claims
1. A method for preparing lysine granules, characterized in that, Includes the following steps: Inner layer preparation: L-lysine hydrochloride and microcrystalline cellulose are mixed at 500-800 rpm, then an adhesive solution is added, and the mixture is stirred until it reaches a soft state. After drying, the first-stage particles are obtained. Intermediate coating: Glycerin, sodium bicarbonate, and alcohol solution A are mixed to obtain an intermediate coating solution; the intermediate coating solution is sprayed onto the surface of the first-stage particles, and the coating weight gain is controlled at 8-12%; then dried and cured to obtain the second-stage particles; Outer layer preparation: Eudragit L100, anti-adhesion agent, plasticizer, and alcohol solution B are mixed to obtain an outer coating liquid; then the outer coating liquid is sprayed onto the surface of the second-stage particles, and the coating weight gain is controlled at 15-20% to obtain the lysine particles.
2. The method for preparing lysine particles according to claim 1, characterized in that, The mass ratio of the L-lysine hydrochloride to the microcrystalline cellulose is 1:(1.2-1.5).
3. The method for preparing lysine particles according to claim 1, characterized in that, The adhesive solution includes one or a mixture of two of the following: an aqueous solution of hydroxypropyl methylcellulose, an aqueous solution of sodium carboxymethyl cellulose, and an aqueous solution of hydroxypropyl cellulose. The adhesive solution has a mass concentration of 5-10%.
4. The method for preparing lysine particles according to claim 1, characterized in that, The glycerol is 15-25% and the sodium bicarbonate is 0.1-0.5% by mass percentage of the intermediate coating solution.
5. The method for preparing lysine particles according to claim 1, characterized in that, When spraying the intermediate coating liquid onto the surface of the first-stage particles, the intermediate coating liquid is sprayed at a rate of 6-8 mL / min, while hot air at 40-45℃ is introduced for drying.
6. The method for preparing lysine particles according to claim 1, characterized in that, The drying and curing conditions for the middle layer coating are 25-35℃ for 3-5 hours.
7. The method for preparing lysine particles according to claim 1, characterized in that, The outer coating liquid comprises, by mass percentage, 5-15% Eudragit L100, 1-3% anti-adhesive, and 0.1-1% plasticizer.
8. The method for preparing lysine particles according to claim 1, characterized in that, When spraying the outer coating liquid onto the surface of the particles in the second stage, the outer coating liquid is sprayed at a rate of 4-6 mL / min, while hot air at 35-40℃ is introduced for drying.
9. The method for preparing lysine particles according to claim 1, characterized in that, After the outer layer is prepared, it is placed at room temperature for 12-36 hours to obtain the lysine particles.
10. Lysine particles obtained by the preparation method of lysine particles according to any one of claims 1-9.
Citation Information
Patent Citations
Novel pH-dependent colon-specific drug delivery system
CN101209246A
Aspirin and clopidogrel hydrogen sulfate compound preparation and preparation method thereof
CN112587495A
Protected compositions comprising two coating layers
WO2019209261A1